Research on the correlation between the size of condyle and occlusion plane in skeletal Class II malocclusions - Hainan Hu; Wanrong Lin; Jun Wu; Haisong Xu (Wiley, 2022)
Abstract Objectives This study was designed to investigate the relationship between the morphological structure of condyle and occlusal plane in skeletal Class II malocclusions by imaging measurement. Materials and Methods This study included 65 skeletal Class II adult patients (18-35 years old) who met the criteria, and all were taken with cone beam computed tomography (CBCT) images (skeletal Class II high angle 38 cases, average angle 18 cases, and low angle nine cases). The statistical methods of mean standard deviation, Pearson correlation, and analysis of variance were used to study the correlation between the size of the condyle and occlusal plane in skeletal Class II malocclusion. Results The FMA and SN‐OP between the groups in skeletal Class II malocclusion are considered statistically significant, p < .05 high angle group > average angle group > low angle group, whereas there are significant correlations between FMA, FH‐OP, SN‐OP, and the medial-lateral diameter (MLD) of the condyle, p < .05, showing a negative correlation. The anteroposterior diameter of the condyle has no significant correlation with these angles, and the high‐angle group size is smaller than the other groups. Conclusion In patients with skeletal Class II high angle malocclusion, the MLD and anteroposterior diameters of condyle were smaller than those of average angle and low angle groups, and negatively correlated with the FMA and SN‐OP. That is the steeper occlusal plane, the smaller MLD of the condyle. It suggests whether orthodontists can promote the stability of the morphological structure of the condyle by changing the inclination of the occlusal plane during the orthodontic process.